Efektivitas Mini Poster sebagai Media Promosi Kesehatan terhadap Perilaku Cuci Tangan Pakai Sabun pada Siswa Sekolah Dasar - Kamariah Kamariah; Rosalia Putri; Dian Rahayu (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
The prevalence of correct handwashing behavior with soap in Aceh Province is 36%. School-age children are the time to instill PHBS values ​​and have the potential to be agents of change to promote PHBS both in the school environment, family, and society. The impact of lazy handwashing with soap can cause various diseases such as diarrhea, flu, hepatitis A, and impetigo (a contagious infection that usually occurs in children who rarely wash their hands, this disease is characterized by red skin which then develops into small blisters). The purpose of this study is to determine the effectiveness of mini posters as a health promotion media on handwashing behavior with soap in elementary school students. The research method is one group pretest posttest design. The sampling technique is total sampling, while the number of samples in this study was 80 students from grades 5 and 6 of elementary school. The results of the study obtained before the intervention of mini posters washing hands with soap behavior of elementary school students 77.5% of students did not wash their hands with soap after urinating and defecating. After the intervention of mini posters washing hands with soap behavior of elementary school students 87.5% did wash their hands with soap. There is an effect of mini poster intervention on increasing handwashing behavior in elementary school students with a p value of 0.000 < 0.05. The results show that mini posters are a reference for the effectiveness of health promotion in preventing infectious diseases in elementary school children by implementing a handwashing program with soap in the school environment